Exact solutions for fractionalized second grade fluid flows with boundary slip effects - Dehraj, Sanuallah; Malookani, Rajab; Aasoori, Sunny Kumar; Bhutto, G.M.; Arain, L. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an exact analytical solution for the motion of fractionalized second grade fluid flows moving over accelerating plate under the influence of slip has been obtained. A coupled system of partial differential equations representing the equation of motion has been re-written in terms of fractional derivatives form by using the Caputo fractional operator.
Keywords: second grade fluid; Caputo fractional operator; slip effects; discrete Laplace transform